KEBERHASILAN LAYANAN KONSELING INDIVIDUAL DITINJAU DARI ASPEK DUKUNGAN SOSIAL SEKOLAH DAN RASA PERCAYA DIRI KONSELI - Mindarti, Dwi Prasetyani; Widodo, Bernardus (Educatio Vitae, 2017)
The successfulness of individual counseling service becomes the important thing for  student. The factors that affect the student are the aspect from supporting surroundings school aspect and the counselee’s self-confidence. The population that is used for this research is the students from the 8th grade of SMP Negeri 12 Madiun, 2016/2017 period. There are 70 (seventy) students that have gotten the individual counseling service from August 2016 up to November 2016 (based on school counselor’s data). So the sample that is used is based on the population, there are 70 (seventy) students. The sampling technique that is used by the writer is Census technique. Technique of data collecting in this research is done by using questionnaire in scale form, that are: The successfulness of individual counseling service, Supporting aspect scale in school surroundings, andcounselee’s self-confidence scale. In this research, the writer has three statement of the problems, that are: (1) First minor hypothesis stated as : There is a significant effect between supporting surroundings school aspect to the successfulness of individual counseling service., (2) Second minor hypothesis stated as: There is a significant effect between counselee’s self-confidence to the successfulness of individual counseling service., (3) Major hypothesis stated as: there is a significant effect between supporting surroundings school aspect and counselee’s self-confidence to the individual counseling service. The data are analyzed by using multiple linear regression. Equality line regression model Y = 19,792 + 0,687 + 0,172 . The result of the analysis thw shows that: (1) there is a positive effect in supporting surroundings school aspect to the successfulness of the individual counseling service, proved t hitung> t tabel(5,742 > 1,99), (2) There is a positive effect in counselee’s self-confidence to the successfulness of individual counseling service, proved t hitung> t tabel(0,980 < 1,99)  , (3) There is a positive effect in supporting surroundings school aspect and counselee’s self-confidence to the individual counseling service, proved F hitung> F tabel(21,533 > 3,134). Based on these result, it can be concluded that : (1) because t hitung> t tabel = 1,99, the first minor hypothesis is accepted, (2) because t hitung<t tabel = 1,99 , the second minor hypothesis is not accepted, (3) because F hitung>F tabel = 3,134 , the major hypothesis is accepted.